Geotechnical properties of some tidal flat sediments of Khor-Abdullah coast, southern Iraq - Muttashar, W.R.; Al-Tai, M.A.; Al-Amari, F.K.; Ali, A.H. (Mesopotamian Journal of Marine Sciences, 2022)
This research involves geotechnical studies for some tidal flat sediments of Khor-Abdulla coast in the southern Basra city. This area has an important strategic location in future, the Iraqi Government intending to establish large engineering projects such as a big Basrah port. Sediment samples have been taken at a depth of 1.25 m to study the physical, chemical, and engineering properties of this region’s sediment. The investigation results reveal that its average high natural moisture was 37.5 %, Liquid Limit LL 45.5 %, Plastic Limit PL 26.5 %, Plasticity Index PI 19%. Hence, these sediments show high clay percentages (85-65%). It can be classified as Silty Clay sediments with low plasticity. Engineering tests resulted in average Compression Strength of 206 kN/m2, Max. dry density 1.63 g/cm3 while consolidation coefficient 0.15 m2/year, consolidation index (0.28) with initial consolidation 35.5 kN/m2, and swelling index 0.071. These factors indicate a week sediment with low plasticity. Chemical tests results reveal high concentrations of sulfates chlorides, and organic matters. TDS were 30666 mg/l, CaCO3 41 mg/l, sulfate 2987 mg/l, Mg 600 mg/l, Ca 46.6 mg/l, and chlorides 1334.2 mg/l. while EC 44.5 mmhos/cm, pH 7.7.